Exploring the awareness of organic food consumption in Algeria: a gender based-study - Chems Eddine Boukhedimi; Abderrahmane Batache; Noureddine Sahali; Yacine Redjouani (Менеджмент та підприємництво: тренди розвитку, 2025)
Organic foods have greatly increased in recent years as people become more concerned about their health, the environment, and the sources of their food. These foods are produced in ways that emphasize natural processes while avoiding the use of synthetic chemicals including pesticides, fertilizers, antibiotics, and genetically modified organisms. Hence, green consumers frequently prefer organic foods for a variety of reasons, including purported health benefits, superior flavor, environmental concerns, and animal welfare. Organic foods can be more expensive than conventionally produced meals, but many people believe the advantages exceed the costs.